Interactive resources to promote self-assessment skills and independent learning: The case of the Spanish English professional and academic communication course - Benali Taouis, Hanane; López Pérez, Sidoní (IGI Global, 2026)
Gamification has proven to be an effective educational tool. This tool becomes even more powerful when combined with challenge-based learning methodologies, which facilitate deeper content acquisition, and develop critical thinking skills. This study is the outcome of an Educational Innovation Project carried out at the Universidad Politécnica de Madrid (2023-2024), which is aimed at creating interactive materials for students enrolled in the course English for Professional and Academic Communication. The developed materials include audiovisual presentations and interactive challenges designed to promote independent learning. We developed interactive presentations by using Genially. Then, Amazon Polly was employed to add voiceovers to these presentations to ensure clearer understanding. At the same time, Genially was also used to create Escape Rooms. These challenges acted as self-assessment tools, incorporating questions about the Genially presentations. The participants found the audiovisual materials and the interactive challenges a useful resource for learning and assessment.
Keywords: self-assessment; interactive resources; independent learning; English; Spanish